PROVERBS AND SAYINGS INTERRELATIONS IN SHUKUR KHOLMIRZAEV’S WORKS (Scientific journal of the Fergana State University, 2023)
The investigation of literary  tasks  and places in Sh.Kholmirzayev’s novels which conveyed folkloristic models about the history of folkloristics and spiritual development as well as the expression of  specific skill demonstrates writer`s opinion about national value as one of the important problems in this article.